RANCANGAN E-MAP BERBASIS DIGITAL SEBAGAI MEDIA INFORMASI WISATA RAFTING DI GRAVITY ADVENTURE PANGALENGAN - Muhammad Tegar (STAH Dharma Sentana Sulawesi Tengah, 2026)
Adventure tourism, such as white water rafting, is increasingly in demand in Indonesia, including at Gravity Adventure Pangalengan. However, limited information for tourists is an obstacle in accessing and understanding the routes and facilities available. This research aims to design a digital-based e-map as a more interactive and informative rafting tourism information media. The method used is mixed method, involving interviews, surveys, and the creation of e-maps using GIS technology and interactive videos. This e-map presents rafting routes, important points, public facilities, and SOPs in digital form integrated into a URL (Uniform Resource Locator). Test results using the System Usability Scale (SUS) showed a score of 70.88, exceeding the average standard of 68, with an “OK” category and a “Marginal” level of acceptance. This indicates that the e-map is quite effective as an information medium, although it still requires improvements in visual aspects and ease of navigation to enhance the overall user experience.